Analysis of various data security techniques of steganography: A survey. Issue 2 (4th March 2021) - Dhawan, Sachin; Gupta, Rashmi
ABSTRACT: The amount of data exchanged via the Internet is increasing nowadays. Hence, data security is termed as a serious issue while communication of data is processed over the Internet. Everyone needs their data to be safe during the process of communication. Steganography is the process of hiding a message, audio, image, or video by embedding it into another image, audio, message, or video. It is employed to protect secret data from malicious attacks. This paper presents a categorization of the steganography based on technical and non-technical steganography and also categorized based on its domain. Issues related to steganography are quality of stego images, payload capacity, mean square error, structural similarity (SSIM), Image Fidelity (IF), and Normalized Cross-Correlation (NCC) and robustness. Researchers have already done commendable research in the area of image steganography. Still, it is important to feature the upsides and downsides of the current systems of steganography. The objective of the paper is to examine and scrutinize the different algorithms of steganography based on parameters like PSNR, MSE, and Robustness. Based on the analysis of these parameters and all the issues, this paper concludes with recommendations for producing high-quality stego images, high-payload capacity, and robust techniques of steganography.